Catalogue of Meteorites from South America - Acevedo, Rogelio Daniel; Rocca, Maximiliano C.L; García, Víctor Manuel (SpringerBriefs in Earth System Sciences, 2014)
The first Catalogue of Meteorites from South America includes new specimens never previously reported, while doubtful cases and pseudometeorites have been deliberately omitted. The falling of these objects is a random event, but the sites where old meteorites are found tend to be focused in certain areas, e.g. in the deflation surfaces in Chile's Atacama Desert, due to favorable climate conditions and ablation processes. Our Catalogue provides basic information on each specimen like its provenance and the place where it was discovered (in geographic co-ordinates and with illustrative maps), its official name, its classification type (class, and if applicable, weathering grade and shock stage), if it was seen falling or was found by chance, its total mass or weight, the institution where it is held, and the most important bibliographic references about it.